2008
DOI: 10.1002/lsm.20626
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Nd:YAG laser‐induced choroidal neovascularization

Abstract: Surgical closure of Nd:YAG induced macular holes should be delayed to allow spontaneous closure. Photodynamic therapy was successful in treating choroidal neovascularization in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Thus, under normal physiological conditions, there is no direct contact between RPE cells and endothelial cells of the choriocapillaries. However, pathologic conditions, such as angioid streaks (irregular crack-like dehiscences in the Bruch's membrane), 16 traumatic choroidal rupture, 1 laser burns, 17 and pathologic myopia, 3 all which are characterized by disruption and disorganization of the retinal pigment epithelium layer and the Bruch's membrane, possibly involving direct EC-RPE contact, are associated with CNV formation. We used a model of EC-RPE coculture that recapitulates the conditions when RPE cells are no longer polarized and ECs are activated; therefore, the physiologic apposition of EC to basal RPE is lost.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, under normal physiological conditions, there is no direct contact between RPE cells and endothelial cells of the choriocapillaries. However, pathologic conditions, such as angioid streaks (irregular crack-like dehiscences in the Bruch's membrane), 16 traumatic choroidal rupture, 1 laser burns, 17 and pathologic myopia, 3 all which are characterized by disruption and disorganization of the retinal pigment epithelium layer and the Bruch's membrane, possibly involving direct EC-RPE contact, are associated with CNV formation. We used a model of EC-RPE coculture that recapitulates the conditions when RPE cells are no longer polarized and ECs are activated; therefore, the physiologic apposition of EC to basal RPE is lost.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for post-injury hole formation, which occurs rarely, is quite different [2], depending on the energy delivered to the retina, but can lead to permanent visual loss unless adequately treated. Secondary macular pucker [3] and choroidal neovascularization [4] have also been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have also reported choroidal neovascularisation, macular hole, and vitreous haemorrhage as severe ophthalmic complications. [2][3][4] When the eye is accidentally exposed to laser radiation, energy is primarily absorbed by the retinal pigment epithelium, which instantaneously causes a temperature increase on the order of thousands of degrees. 7 Consequently, various mechanisms (tissue ionisation, plasma formation and a centrifugally migrating acoustic shock wave) disrupt the retina, retinal pigment epithelium and choriocapillaris.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that most nanosecond Nd: YAG laser-associated ophthalmic complications are choroidal neovascularisation, macular hole, and vitreous haemorrhage. [2][3][4] These complications also have been reported as poor prognosis of visual function.…”
mentioning
confidence: 99%